High-temperature oxidation mechanism of ZrCoSb-based half-Heusler thermoelectric compounds. (10th June 2023) - Gu, Jinyu; Wang, Lei; Song, Qingfeng; Wang, Chao; Xia, Xugui; Liao, Jincheng; Sun, Yi-Yang; Chen, Lidong; Bai, Shengqiang
Highlights: Three typical layers of oxidation products tend to form on the surface, namely, the dense oxide layer (DOL) composed of (Zr, Hf)O2 and CoSb, the alternate oxide layer (AOL) composed of repeated (Zr, Hf)O2 and CoSb2 O6 /Co3 O4, and the CoSb layer between the DOL and AOL. The mass gain during oxidation is mainly caused by the rapid growth of the AOL, which is controlled by the outward diffusion of Zr/Hf and inward diffusion of oxygen. The formation of continuous CoSb layer and DOL can block the outward diffusion of Zr and Hf. A simple approach is proposed to improve the oxidation resistance by pre-oxidizing the sample in low oxygen pressure to form the dense (Zr, Hf)O2 and CoSb layers as oxidation protecting and/or diffusion blocking layers. Abstract: ZrCoSb-based half-Heusler (HH) compounds are among the most promising thermoelectric (TE) materials for high-temperature power generation. Oxidation resistance is one of the key issues for realizing the practical application of TE materials for long-term service in the ambient working environment. In this work, the oxidation behavior of Zr0.5 Hf0.5 CoSb0.8 Sn0.2 (ZHCSS) half-Heusler is systematically studied in the service temperature range from 873 to 1073 K. It is revealed that three typical layers of oxidation products tend to form on the surface of HH sample, namely, the dense oxide layer (DOL) composed of (Zr, Hf)O2 and CoSb, the alternate oxide layer (AOL) composed of repeated (Zr, Hf)O2 and CoSb2 O6 /Co3 O4, and the CoSb layer between the DOL and AOL. The mass gain during oxidation is mainly caused by the rapid growth of AOL, which is controlled by the outward diffusion of Zr/Hf and the inward diffusion of oxygen. The formation of a continuous CoSb layer and DOL is found beneficial to block the outward diffusion of Zr/Hf. Based on the analysis of the dominant factors on the outward and inward diffusions as well as the reaction activation energy, a simple approach is proposed to improve the oxidation resistance of Zr0.5 Hf0.5 CoSb0.8 Sn0.2 by pre-oxidizing the sample in low oxygen pressure to form the dense (Zr, Hf)O2 and CoSb layers as oxidation protecting and/or diffusion blocking layers. The oxidation test shows the effectiveness of such pre-oxidation on the formation and growth of the AOL and therefore on improving the service stability of Zr0.5 Hf0.5 CoSb0.8 Sn0.2 at high temperatures in the air.